Factors associated with patient safety culture domains in perioperative units (Research, Society and Development, 2020)
Objective to analyze the factors associated with the domains of patient safety culture in perioperative units from the perspective of health professionals. Method: cross-sectional study, developed with 146 health professionals from perioperative units of a teaching hospital in Rio Grande do Sul, Brazil, from March to July 2018. Data were collected through the Brazilian version of the Safety Attitudes Questionnaire (SAQ), consisting of six domains. Values of means ≥75 points are considered to be a positive assessment of the safety culture. For data analysis, descriptive and bivariate statistics were used. Results: the domain that had the best evaluation among professionals was Job Satisfaction (score = 83.0). The Unit Management Perception (score = 55.2) and Hospital (score = 47.6) domains obtained the worst assessments. There was an association (p